2023
DOI: 10.3390/v15020408
|View full text |Cite
|
Sign up to set email alerts
|

The Spread of SARS-CoV-2 Omicron Variant in CALABRIA: A Spatio-Temporal Report of Viral Genome Evolution

Abstract: We investigated the evolution of SARS-CoV-2 spread in Calabria, Southern Italy, in 2022. A total of 272 RNA isolates from nasopharyngeal swabs of individuals infected with SARS-CoV-2 were sequenced by whole genome sequencing (N = 172) and/or Sanger sequencing (N = 100). Analysis of diffusion of Omicron variants in Calabria revealed the prevalence of 10 different sub-lineages (recombinant BA.1/BA.2, BA.1, BA.1.1, BA.2, BA.2.9, BA.2.10, BA.2.12.1, BA.4, BA.5, BE.1). We observed that Omicron spread in Calabria pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 65 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…We enrolled 14 consecutive patients tested positive for SARS-CoV-2 with mild to severe COVID-19 [ 23 ] from January 24th to July 7th, 2022. At that time the Omicron variants were predominant in our setting in Calabria region, Southern Italy [ 24 ]. Patients with mild COVID-19 symptoms for a maximum of 7 days who did not require oxygen support presented to the center dedicated to early therapies for COVID-19 [ 25 ] to receive neutralizing monoclonal antibodies (moAbs) or antivirals (i.e., remdesivir, nirmatrelvir/ritonavir or molnupiravir).…”
Section: Resultsmentioning
confidence: 99%
“…We enrolled 14 consecutive patients tested positive for SARS-CoV-2 with mild to severe COVID-19 [ 23 ] from January 24th to July 7th, 2022. At that time the Omicron variants were predominant in our setting in Calabria region, Southern Italy [ 24 ]. Patients with mild COVID-19 symptoms for a maximum of 7 days who did not require oxygen support presented to the center dedicated to early therapies for COVID-19 [ 25 ] to receive neutralizing monoclonal antibodies (moAbs) or antivirals (i.e., remdesivir, nirmatrelvir/ritonavir or molnupiravir).…”
Section: Resultsmentioning
confidence: 99%
“…Multicentric studies are needed to understand if our results are confirmed in different settings across Italy. Second, despite the fact that there was a lack of data about SARS-CoV-2 variants of concern (VoCs) and subvariants in individual patients, the general picture and evolution are well known in our region since an epidemiological survey coordinated by our center demonstrated that in August 2021, Delta was the only circulating variant, while as of January 2022, Omicron subvariants emerged and took over Delta ( 45 , 46 ). Therefore, SARS-CoV-2 variants and subvariants do not appear to be a reasonable explanation for the increase of the inpatients mortality during the fourth wave, because Omicron variants/subvariants prevailed in this period, being already associated with reduced virulence, particularly in patients who received full vaccination course ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the L5F is disadvantageous for the SARS-CoV-2 virus because the mutated epitope could enhance CD8 T cell recognition and killing through this improved interaction [63]. Additionally, it was the only unusual substitution to appear in BA.2 and BA.5 sub-lineages among 272 positive samples isolated in Southern Italy [64]. The L18F substitution is of significance because it has been found to compromise binding of neutralizing antibodies, allowing a much faster propagation in the presence of plasma antibodies collected from donors infected in the previous wave of the epidemic [65].…”
Section: Discussionmentioning
confidence: 99%